Contraband and Counterfeit of Tobacco Products in Digital Age - Tagarev, Nedko (Research Papers, 2020)
In the first part in this paper are shown the basics of conventional C&C of tobacco products aspects. In second part is shown the changes that provide digital technologies in illicit trade of tobacco products. There are provided some examples and some cases.
Keywords: Contraband & Counterfeit; Tobacco; Digital; Internet; online